What Determines the DPRK’s Anthracite Exports to China?: Implications for the DPRK’s Economy - 이종규 (14185, 2015)
Anthracite exports have special value within the DPRK’s economy. In this paper, we focus on what determines the DPRK’s anthracite exports to China. We use panel data consisting of cross-section data from 30 provinces in China and quarterly time-series d